The Moral Humanity in Rawson Marshall Thurbers’ Film Skyscraper - M. Afan; Sukardi; Baiq Indah Nurmayanti; Anisa Nur'aini (Penaoq: Jurnal Sastra, Budaya dan Pariwisata, 2024)
Analysis of moral humanity in film Skyscraper is a study that explains the moral message. In this study, of course, using a qualitative descriptive research method, namely researchers will make direct observations of moral messages. The research object used by researchers is An Analysis of Moral Humanity in Rawson Marshall Thurbers Skyscraper Film. Where this film was produced by Beau Flynn directed by Rawson Marshall Thurbers because it tells about phenomena inherent in everyday life such as kinship, responsibility, courage, mutual trust, love, help, and honesty. The data collection technique used in this study was documentation analysis. Where the researcher captures several scenes that contain moral messages to be conveyed to the public. The results found in this film based on the theory of Roland Barthes are to analyze the meaning of signifiers, denotative, connotative, and mythical meanings. The results of this study show 7 scenes that show elements of the moral message in the Skyscraper film. So the researchers found the hidden meaning of the film in the form of a moral message.